Current Advances in Nanotechnology-Mediated Delivery of Herbal and Plant-Derived Medicines - Amir Jalili; Rafieh Bagherifar; Ali Nokhodchi; Barbara Conway; Yousef Javadzadeh (Tabriz University of Medical Sciences, 2023)
Phytomedicine has been used by humans since ancient times to treat a variety of diseases. However, herbal medicines face significant challenges, including poor water and lipid solubility and instability, which lead to low bioavailability and insufficient therapeutic efficacy. Recently, it has been shown that nanotechnology-based drug delivery systems are appropriate to overcome the above-mentioned limitations. The present review study first discusses herbal medicines and the challenges involved in the formulation of these drugs. The different types of nano-based drug delivery systems used in herbal delivery and their potential to improve therapeutic efficacy are summarized, and common techniques for preparing nanocarriers used in herbal drug delivery are also discussed. Finally, a list of nanophyto medicines that have entered clinical trials since 2010, as well as those that the FDA has approved, is presented.